2023
DOI: 10.1007/s12011-023-03610-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched Bacillus subtilis Improves Growth Performance, Antioxidant Capacity, Immune Status, and Gut Health of Broiler Chickens

Abstract: This study aimed to investigate the effects of selenium (Se) -enriched Bacillus subtilis (Se-BS) on growth performance, antioxidant capacity, immune status and gut health in broilers. A total of 240 day-old Arbor Acres broilers were randomly allotted to four treatments of a basal diet supplemented with no Se, sodium selenite (SS), B. subtilis (BS), and Se-BS and raised for 42 days. The results showed that Se-BS supplementation signi cantly increased body weight (BW), average daily gain, the activities of super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Room temperature was controlled at 32-35°C for 3 days, and then gradually reduced by 3°C/week until it reached 24°C, where it was maintained for the remainder of the experiment. A previous study from our group had revealed that the average daily feed intake was similar in both groups, but the feed conversion ratio was lower for chickens fed SS, BS, and Se-BS (20).…”
Section: Animals and Experimental Treatmentsmentioning
confidence: 56%
“…Room temperature was controlled at 32-35°C for 3 days, and then gradually reduced by 3°C/week until it reached 24°C, where it was maintained for the remainder of the experiment. A previous study from our group had revealed that the average daily feed intake was similar in both groups, but the feed conversion ratio was lower for chickens fed SS, BS, and Se-BS (20).…”
Section: Animals and Experimental Treatmentsmentioning
confidence: 56%
“…Some studies have reported that antioxidant function is closely related to immune function, and a reduction in the antioxidant function of an organism will lead to an increase in oxygen free radicals and others. In addition, the occurrence of the lipid peroxygenation reaction will cause peroxygenation damage to the body tissue, causing cell metabolism disorders and an immunity decline [ 41 , 42 , 43 , 44 , 45 ]. In this study, the detected immune and antioxidant indices in the serum confirmed that the changing trend in antioxidant and immune functions was consistent, which was also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results indicated that adding SeNPs rich L11 bacterial agent to feed can significantly improve the immunity of sheep. Compared with the control group, broilers supplemented with Se-rich B. subtilis not only gained weight, but also increased enzyme activities such as the GPx, CAT, POD, and plasma levels of IL-2, IL-4, and IgG, while plasma MDA levels decreased [32]. After oral administration, some B. subtilis strains can colonize the intestinal mucosa of animals, optimize the composition of intestinal microbiota, and effectively stimulate immunity and metabolism.…”
Section: Preliminary Study On the Application Of L11 To Produce Senpsmentioning
confidence: 98%